METHODOLOGY FOR TEACHING UNITS OF MASS AND VOLUME IN PRIMARY CLASSES - Abdullayeva Barno Sayfutdinovna; Mamadjanova Muslima (Research Focus International Scientific Journal, 2024)
This study explores an innovative methodology for teaching units of mass and volume in primary classes. The research aims to enhance young learners’ comprehension through a structured approach that combines interactive lectures, practical demonstrations, and group activities. Customized educational materials and pre/post-assessment tests were utilized to measure the effectiveness of the methodology. Results indicate significant improvements, providing valuable insights for educators. The discussion interprets findings within pedagogical theories, addressing methodology strengths and limitations. This research contributes to primary education by offering a systematic approach to improve understanding of mass and volume concepts.